The effect of nearpod-assisted problem-based learning on environmental literacy - Nurjanah, Rini; Agustian, Dita; Ali, Mufti (JPBIO (Jurnal Pendidikan Biologi), 2025)
The lack of interactive and contextual learning models further weakens student engagement with environmental issues. This study aims to determine the effect of the Problem-Based Learning (PBL) model assisted by Nearpod on students' environmental literacy regarding climate change material in Grade 10 at SMA Negeri 10 Tasikmalaya. The research method used is a Quasi-Experimental design. The research population consists of 10 classes, with a purposive sampling method yielding a sample size of 2 classes, comprising an experimental class and a control class. The research instruments used tests and non-tests in the form of multiple-choice questions and questionnaires. The results of the ANCOVA test showed that the Nearpod-assisted PBL model had a significant partial effect on environmental literacy in the cognitive and affective indicators, with a significance value of 0.000, but did not show an effect on the behavioral indicator, which obtained a significance value of 0.874. Meanwhile, the simultaneous test results for the combined three environmental literacy indicators yielded a significance of 0.184 (p-value > 0.05), indicating that the implementation of the Nearpod-assisted PBL model has not yet been able to provide a comprehensive impact on environmental literacy among students at SMAN 10 Tasikmalaya.